2004
DOI: 10.1097/00004694-200401000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Osteomyelitis in Children Resistant to Previous Therapy

Abstract: Patients admitted to the authors' institution with tibial osteomyelitis between 1978 and 1998 were reviewed. The purpose of this study was to determine the incidence, etiology, treatment, and outcome in chronic pediatric tibial osteomyelitis. The authors describe their treatment of chronic osteomyelitis in children resistant to previous therapeutic modalities. Thirty patients were identified with a mean age of 8.5 years at diagnosis. Mean age at admission was 9.6 years, indicating more than a 1-year duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
1
12
1
Order By: Relevance
“…Surgical specimens provided a positive culture in 85.5% of the cases, which again is comparable to previous reports. 29,30 Whereas other studies have reported culturenegative specimens in 15% to 47% of cases diagnosed primarily using bone scans, 1,17,18,33,34 only 15.5% of our surgical specimens failed to produce bacterial growth.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Surgical specimens provided a positive culture in 85.5% of the cases, which again is comparable to previous reports. 29,30 Whereas other studies have reported culturenegative specimens in 15% to 47% of cases diagnosed primarily using bone scans, 1,17,18,33,34 only 15.5% of our surgical specimens failed to produce bacterial growth.…”
Section: Discussioncontrasting
confidence: 59%
“…17,30 We used multiple irrigation and debridement procedures in addition to intravenous antibiotics as an aggressive therapeutic means. Most patients seen at the Children's Hospital were treated according to similar protocols combining antibiotic chemotherapy and surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-reactive protein (CRP) was recorded in 137 (71.7%) patients with a mean of 80 mg/L (range, <1 to 380 mg/L). In 10 Table 2. Rates of MRSA (5.1%) and extended spectrum beta lactamase (3.4%) were low (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The literature contains many pediatric series of acute hematogenous osteomyelitis (AHO), [1][2][3][4][5][6][7][8][9] but few recent studies focus solely on tibial infection. 10 Osteomyelitis can result from hematologic spread or from direct inoculation. The tibia is predisposed to infection due to the characteristics of its metaphyseal blood supply, 11 and because it is the most frequent site of open fractures.…”
mentioning
confidence: 99%